Fatal Adverse Events Associated with Pembrolizumab in Cancer Patients: A Meta-Analysis. (7th February 2020) - Sher, Amna F.; Golshani, Gol M.; Wu, Shenhong
Abstract: Background: Pembrolizumab as an immune checkpoint inhibitor (ICI) has emerged as an effective treatment for many cancers. It has unique immune-related adverse events (irAE) and little is known about its risk of fatal adverse events (FAEs). We conducted a meta-analysis of clinical trials to determine the incidence and risk of FAEs with pembrolizumab. Methods: A systematic search for phase I–III clinical trials of pembrolizumab was conducted using databases including PUBMED and abstracts presented at the American Society of Clinical Oncology (ASCO) conferences until October 2018. Eligible studies included prospective clinical trials of pembrolizumab with available data on FAE. Data on FAE was extracted from each study and pooled for calculations. Incidence, relative risk (RR) and 95% confidence intervals (CI) were calculated by employing fixed or random-effects models. Results: A total of 11 clinical trials with 3713 patients were included for analysis. The overall incidence of FAE with pembrolizumab was 1.2% (95% CI: 0.5–2.8%). The incidence of FAE significantly varied among different tumor types ( p  = .02), ranging from 0.2% in melanoma to 3.1% in breast cancer, and with its combination with chemotherapy (0.7%, 95% CI: 0.4–1.2% versus 7.0%, 95% CI: 4.9–10%; p <.01). Chemotherapy plus pembrolizumab 7.0% (95%CI: 4.9–10) as compared to pembrolizumab alone 0.7%, (95% CI: 0.4–1.2; p  < .001). There was no significant difference in the risk of FAEs when pembrolizumab was compared with chemotherapy with RR = 1.24 (95% CI: 0.8–1.89; p  = .31). The most common FAEs were due to infectious complication (26.5%), cardiac toxicity (14.7%) and pneumonitis (13.2%). Conclusions: The risk of FAEs with pembrolizumab may be similar to chemotherapy in cancer patients and may vary with tumor types and its combination with chemotherapy.